Three Novel Entomopathogenic Fungi From China and Thailand - Wei, De-Ping; Wanasinghe, Dhanushka N.; Xu, Jian-Chu; To-anun, Chaiwat; Mortimer, Peter E.; Hyde, Kevin D.; Elgorban, Abdallah M.; Madawala, Sumedha; Suwannarach, Nakarin; Karunarathna, Samantha C.; Tibpromma, Saowaluck; Lumyong, Saisamorn (Frontiers in Microbiology, 2021)
Entomopathogenic fungi are ubiquitous in trophic rainforests and feature a high level of diversity. This group of fungi not only have important ecological value but also medicinal value. Nevertheless, they are often ignored, and many unknown species have yet to be discovered and described. The present study aims to contribute to the taxonomical and phylogenetic understanding of the genus by describing three new species, which were collected from Guizhou and Yunnan Provinces in China and Krabi Province in Thailand. The three novel species named Paraisaria alba, P. arcta and P. rosea share similar morphologies as those in the genus Paraisaria, containing solitary, simple, fleshystroma, completely immersed perithecia and cylindrical asci with thickened caps and filiform ascospores that often disarticulate at maturity. Phylogenetic analysis of combined LSU, SSU, TEF, RPB1, RPB2 and ITS sequence data afterwards confirm their placement in the genus Paraisaria. In this study, the three entomopathogenic taxa are comprehensively described with colour photographs and phylogenetic analyses. A synopsis table and a key to all treated species of Paraisaria are also included.